TANGGUNG JAWAB DINAS SOSIAL KOTA PEKANBARU TERHADAP PENYANDANG DISABILITAS TERKAIT KONSEP KESEJAHTERAAN BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 18 TAHUN 2013 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN PENYANDANG DISABILITAS - Lili Rahayu; Emilda Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The implementation of social welfare is aimed at improving the quality of life and social welfare, including for people with disabilities. The duty of local governments to provide welfare for persons with disabilities is stated in the Riau Province Regional Regulation Number 18 of 2013 concerning the Protection and Empowerment of Persons with Disabilities. In it, it explains the rights for persons with disabilities that they should accept and also the obligations of local governments to make it happen by providing protection and empowerment. Based on the background description that has been described above, the authors are interested and raise this issue in the form of a thesis entitled "The Responsibility of the Pekanbaru City Social Service for Persons with Disabilities Related to the Concept of Welfare Based on Riau Province Regional Regulation Number 18 of 2013 concerning Protection and Empowerment of Persons with Disabilities. ". This type of legal research used by researchers is a type of empirical or sociological legal research. Sources of data used were obtained through 3 (three) legal materials, namely primary, secondary and tertiary legal materials. The data collection techniques were carried out using methods, namely questionnaires, interviews and literature review. From the results of research and discussion it can be concluded that First, the responsibility of the Pekanbaru City Social Service has not been implemented properly. Rehabilitation, providing courses and training, capital, assisting in business management have not been implemented properly. Second, the inhibiting factor for the Pekanbaru City Social Service is the vacant position at the Head of the Rehabilitation Section for Persons with Disabilities, the absence of social institutions, limited budgets, limited assistants with disabilities, and the absence of enforcement of the Pekanbaru City Regional Regulation Number 12 of 2008 concerning Social Order. Keywords: Responsibility - Social Service - Persons with Disabilities - Welfare